Transparent-to-dark photo- and electrochromic gels. Issue 1 (December 2018) - Gonzalez, Laura; Liu, Chung; Dietrich, Bart; Su, Hao; Sproules, Stephen; Cui, Honggang; Honecker, Dirk; Adams, Dave; Draper, Emily
Abstract Smart windows in which the transmittance can be controlled on demand are a promising solution for the reduction of energy use in buildings. Windows are often the most energy inefficient part of a building, and so controlling the transmittance has the potential to significantly improve heating costs. Whilst numerous approaches exist, many suitable materials are costly to manufacture and process and so new materials could have a significant impact. Here we describe a gel-based device which is both photo- and electrochromic. The gel matrix is formed by the self-assembly of a naphthalene diimide. The radical anion of the naphthalene diimide can be formed photo or electrochemically, and leads to a desirable transition from transparent to black. The speed of response, low potential needed to generate the radical anion, cyclability of the system, temperature stability and low cost mean these devices may be suitable for applications in smart windows. Materials with switchable colour and opacity hold promise as components of 'smart windows'. Here a photo- and electrochromic device based on a self-assembled naphthalene diimide gel is shown to undergo reversible photo or electrochemical transition from transparent to black.